Notes on the genus Tylophora R. Br. (Asclepiadaceae) of India (Bangladesh Journal of Plant Taxonomy, 2018)
A new subspecies, Tylophora perakensis King & Gamble subsp. andamanica isdescribed and illustrated from Little Andaman Island, Andaman and Nicobar Islands, India. A new combination, Tylophora hookeriana is proposed and the distributional status of T. indica Merr. var. intermedia M.A. Rahman & Wilcock is also discussed based on the fresh collections from Andaman Islands. Bangladesh J. Plant Taxon. 25(1): 51-56, 2018 (June)